2020
DOI: 10.17478/jegys.650400
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Problem Based Learning and Tacit Knowledge on Problem-Solving Skills of Students in Computer Network Practice Course

Abstract: This study aims to examine the effect of problem-based learning and tacit knowledge on problem-solving skills when students study in the laboratory. The method employed in this research was Quasi-Experimental Design. Data collection techniques were questionnaires and tests. Seventy-seven students were taken as the research participant and divide into two groups; 35 students in the experimental group with problem-based learning implementation and 42 students in the control group with procedural instruction. Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Tacit knowledge is more fundamental than explicit knowledge. It was found that students with high tacit knowledge gained higher academic achievement than those with low tacit knowledge ( Chamidy et al, 2020 ). Besides, tacit knowledge as an experience and skill promote student understanding and solving problems ( Ibidunni et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Tacit knowledge is more fundamental than explicit knowledge. It was found that students with high tacit knowledge gained higher academic achievement than those with low tacit knowledge ( Chamidy et al, 2020 ). Besides, tacit knowledge as an experience and skill promote student understanding and solving problems ( Ibidunni et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through the construction of a tacit knowledge transformation approach, researchers can design student-student interactions that promote a positive classroom climate ( Nurmi and Kiuru, 2015 ). It can also guide tacit knowledge transformation to achieve a higher level of students’ problem understanding and solving ( Chamidy et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As for conducting purely online laboratory for computer networking classes, there is little existing published work as of the writing of this paper. Some related discussion on delivering computer networking lectures online focuses on explaining the theory part with pedagogy methods such as flipped-classroom, but not the online laboratory [18][19][20][21][22].…”
Section: Related Work and Problem Statementmentioning
confidence: 99%